2019
DOI: 10.32098/mltj.02.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

Can arthroscopic revision surgery for shoulder instability be a fair option?

Abstract: Background: the aim of this study was to evaluate the role of arthroscopic capsuloplasty in the treatment of failed primary arthroscopic treatment of glenohumeral instability. Methods: we retrospectively examined at a minimum of 3-years follow-up 22 patients who underwent arthroscopic treatment between 1999 and 2007 who had recurrent anterior shoulder instability with a post-surgical failure. A statistical analysis was performed to evaluate which variable could influence the definitive result and clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…(continued) e6 71 DS 10 (11) Boileau et al 72 DS 6 (7) 8 ( 9) 9 (10) 14 ( 15) Calvo et al 73 DS 11 (18) Kim et al 97 DSA 0 (0) 0 (0) 4 ( 6) 4 (6) Kim et al 74 167 DSA 1 (1) 2 (1) 4 (2) 7 (4) Sperber et al 38 DS 0 7 (23) Nakagawa et al 39 257 DS 42 (16) Nakagawa et al 40 DS 22 (24) Chechik et al 41 DS 9 (11) 7 ( 8) 16 ( 19) Cole et al 98 DSA 3 (8) 9 (24) Anderl et al 42 DSA 0 (0) 0 (0) 0 (0) 0 (0) Constantinou et al 75 DS 6 (19) De Giorgi et al 43 DS 4 (19) 1 ( 5) 3 ( 14 48 Recurrent dislocation, symptomatic subluxation or instability preventing return to full active duties or necessitating an additional surgical stabilization procedure. 2).…”
Section: Critical Appraisal and Definition Of Recurrencementioning
confidence: 99%
“…(continued) e6 71 DS 10 (11) Boileau et al 72 DS 6 (7) 8 ( 9) 9 (10) 14 ( 15) Calvo et al 73 DS 11 (18) Kim et al 97 DSA 0 (0) 0 (0) 4 ( 6) 4 (6) Kim et al 74 167 DSA 1 (1) 2 (1) 4 (2) 7 (4) Sperber et al 38 DS 0 7 (23) Nakagawa et al 39 257 DS 42 (16) Nakagawa et al 40 DS 22 (24) Chechik et al 41 DS 9 (11) 7 ( 8) 16 ( 19) Cole et al 98 DSA 3 (8) 9 (24) Anderl et al 42 DSA 0 (0) 0 (0) 0 (0) 0 (0) Constantinou et al 75 DS 6 (19) De Giorgi et al 43 DS 4 (19) 1 ( 5) 3 ( 14 48 Recurrent dislocation, symptomatic subluxation or instability preventing return to full active duties or necessitating an additional surgical stabilization procedure. 2).…”
Section: Critical Appraisal and Definition Of Recurrencementioning
confidence: 99%
“…Seven studies dating between 2002 and 2014 reported return to play after arthroscopic revision Bankart repair in a total of 153 athletes. 2 – 4 , 9 , 17 , 24 , 28 The average follow-up was 39.1 months (SD, 8.29). Table 1 shows the weighted mean complication rate of 3.3% (range, 0%-6.25%), and Table 2 demonstrates the weighted mean and return-to-play mean rate of 84.0% (range, 56.25%-100%).…”
Section: Resultsmentioning
confidence: 99%
“…6,7 The primary goal of any stabilization procedure is to prevent reccurence of instability and Percentage of failure or recurrence after revision arthroscopic surgery was 36.4%, so an Arthroscopic revision procedure for failed instability surgery may generally be not recommendable. 6,8 The open latarjet operation procedure after failed arthroscopic bankart repair resulted in a low reccurence rate and good functional scores after a minimum of 24 months follow up. 3 Described in 1954 by Latarjet, the essential feature of this procedure was the transplantation of the coracoid process to the neck of the scapula through the subscapularis tendon.…”
Section: Discussionmentioning
confidence: 99%